Economic Welfare Measurements and Human Well-Being. - Offer, A (Nuffield College (University of Oxford), 2000)
GDP per head is not only an economic indicator, but is widely used as a welfare indicator. This use not well founded in economic theory. The paper compares income per head with a three groups of alternative indicators: 'extended national accounts', social indicators, and indicators of subjective well-being. All of these methods indicate a decline in the welfare productivity of GDP goods over time.